Electrochemical behavior of Inconel 718 fabricated by laser solid forming on different sections. (March 2018) - Guo, Pengfei; Lin, Xin; Li, Jiaqiang; Zhang, Yufeng; Song, Menghua; Huang, Weidong
Graphical abstract: Highlights: Electrochemical behavior of laser solid forming Inconel 718 on different sections was investigated for the first time. The correlation between microstructural features and electrochemical behavior was analyzed. A dissolution rate model for the constituent phases has been established. High current density can lead to good surface quality. Abstract: Microstructural analysis and electrochemical behavior of Inconel 718 fabricated by laser solid forming on horizontal section (HS) and vertical section (VS) were investigated. The electrochemical results show that the corrosion resistance on HS and VS have no difference in 10 wt.% NaNO3 solution. However, HS possesses lower surface products resistance at low current densities due to the tube-like distribution of secondary phases. Besides, their higher current efficiencies at low current densities are mainly attributed to the undissolved phases being flushed away by the flowing electrolyte. The fast detachment rates of secondary phases at high current densities improve the surface quality.